An overview on role of unconventional machining processes on different materials. (2022) - Jayappa, Pradeep; Srinivasan, Santhosh; Vetrivel Murugan, K.; Thangavel, C.; Bala Theja, M.; Phanindra Raja Varma, G.; Marichamy, S.; Subbiah, Ram
Highlights: This article describes the unconventional machining processes on different materials. Hard materials are used for machining to get high dimensional accuracy. Machining of complex shapes, micro machining are possible using this process. The efficiency of production and machining precision are enhanced. The different metal removal mechanisms were discussed. The medium of energy are transferred through electrolyte, electron and high voltage particles. Abstract: In present days, the development and applications of unconventional machining processes got rapidly increased in modern industries. The quality and performance of the product are improved through unconventional machining processes. Hard materials are preferred to obtain high dimensional accuracy. The machining of complex shapes, super finishing, micro machining and surface is possible by unconventional machining process. The efficiency of production and machining precision were enhanced. The different types of machining methods were utilized to remove the materials. The different metal removal parameter such as erosion, Ionic dissolution, vaporization were analysed etc. The medium of energy were been transferred through electrolyte, electron and high voltage particles. This review article clearly describes the unconventional machining and hybrid machining processes on different materials.